Canthium simile Merr. & Chun (Rubiaceae), a new species for the flora of Vietnam - Chinh, Vu Tien; Quang, Bui Hong; Cuong, Nguyen The; Bach, Tran The (Academia Journal of Biology, 2012)
The genus Canthium Lamk. (Rubiaceae) in the world has about 200 species distributed in tropical, subtropical Asia and Africa. Vietnam has 9 species of this genus [Tran Ngoc Ninh 2005]. During the time to study specimen on this genus in Hanoi herbarium, we found one new species (Canthium Lamk.) for the flora of Vietnam. The species Canthium simile Merr. & Chun has been discoved from the Vu Xuan Phuong’s of the Institute of Ecology and Biological Resources (HN). Specimens collected from Pu Mat national park, Nge An province. Thus there are 10 species belonging to the genus Canthium Lamk. recorded for the flora of Vietnam. They are Canthium cochinchinense Pierre ex Pitard; C. coffeoides Pierre ex Pitard; C. dicoccum (Gaertn.) Teysm. & Binn.; C. filipendulum Pierre ex Pitard; C. glabrum Blume; C. horridum Blume; C. parvifolium Roxb; C. rheedii DC; C. simile Merr. & Chun; C. umbellatum Wight.